Racionalismo crítico, verdad científica y falibilismo moral en la epistemología de Karl Popper - Gómez Navarro, Ángel (2020)
In this essay the epistemic criterion of fallibilism is analyzed within the critical rationalism and scientific realism that make up the epistemology of Karl Popper. Fallibilism becomes evident especially when evaluating not only scientific theories but also moral theories or various conceptions of good, in order to determine their claims to truth in the context of a plural and democratic society.